1986
DOI: 10.1007/bf02795623
|View full text |Cite
|
Sign up to set email alerts
|

Environmental exposure to cadmium and factors affecting trace-element metabolism and metal toxicity

Abstract: In the general population, food constitutes the major environmental source of cadmium (Cd) in nonsmokers. It is established that leafy vegetables, roots, and grains (wheat or rice) can accumulate relatively high amounts of Cd from the soil. Beef liver and kidney and shellfish are also major dietary sources of Cd. The daily intake of Cd in various parts of the world is different and depends on both the dietary habits and concentration of Cd in foodstuffs. Because of the long biological half-life of Cd in humans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(17 citation statements)
references
References 86 publications
1
16
0
Order By: Relevance
“…The cadmium-zinc, cadmiumcopper, and cadmium-iron interactions are strictly connected and are dependent on the dose of those elements (Church and Pond, 1974;Kabata-Pendias andPendias, 1993, Peraza et al, 1998). The first interactions take place in the gastrointestinal tract during absorption (Chmielnicka and Cherian, 1986;Groten and van Bladern, 1994).…”
Section: Cadmium Influence On the Levels Ofmentioning
confidence: 98%
“…The cadmium-zinc, cadmiumcopper, and cadmium-iron interactions are strictly connected and are dependent on the dose of those elements (Church and Pond, 1974;Kabata-Pendias andPendias, 1993, Peraza et al, 1998). The first interactions take place in the gastrointestinal tract during absorption (Chmielnicka and Cherian, 1986;Groten and van Bladern, 1994).…”
Section: Cadmium Influence On the Levels Ofmentioning
confidence: 98%
“…In addition, Cd is generally found in low concentrations in food, air, water and cigarette smoke (Chmielewska and Cherian, 1986;WHO, 1992;Muller and Anke, 1994). Clinical and experimental studies have demonstrated an embryotoxic action of Cd.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, various blood parameters (McKim et al, 1970;Christensen et al, 1972), enzyme activities in blood (Christensen and Tucker, 1976) and reproduction (Homing and Nieheisel, 1979) are affected. In contrast to Cu, a biological function for Cd is unknown, and the metal is toxic to organisms at very low concentrations (Chmielnicka and Cherian, 1986). For example, exposure to Cd resulted in reduced growth, reproduction and survival in flagfish Jordanella floridae (Spehar, 1976).…”
Section: Introductionmentioning
confidence: 99%